Students' Perceptions On How Journalism Course Improves English Skills: A Case Study Of Midterm Exam Data - Abdul Rohim; Aidil Syahputra (Globish: An English-Indonesian Journal for English, Education, and Culture, 2024)
This study investigates Indonesian university students' perceptions of how a journalism course impacts their English language skills, focusing on midterm exam data. Utilizing a qualitative approach, the research employs a case study design at Universitas Muhammadiyah Tangerang. Data were collected through questionnaires, interviews, document analysis, classroom observations, and focus group discussions. Key findings indicate significant improvements in writing, critical thinking, and speaking confidence. The majority of students (80%) reported enhanced writing abilities, while 70% of midterm exam scores reflected strong performance in grammar, vocabulary, and coherence. Despite these gains, some students highlighted the need for more support in foundational language skills. The study underscores the importance of integrating English language support within content-focused courses to foster holistic English proficiency. Future research should explore long-term impacts and the transferability of skills across different academic and professional contexts.